Internet of Things as Virtual Settlements: Insights from Excavating Social Media Sites - Akoumianakis, D.; Karadimitriou, N.; Vlachakis, G.; Milolidakis, G.; Bessis, N. (2012 4th International Conference on Intelligent Networking and Collaborative Systems, 2012)
The paper explores excavation as a metaphor or conceptual lens for gaining insights to cyber-structures enacted in virtual settlements. More importantly, we vision such excavations in the context of enlarged Internet of Things, an inter-connected world of online remains capable of providing a different lens on how to make sense of cyber-structures linked via and enacted through the Internet. The emphasis is on conditions for virtual excavations, techniques which could be used to support them as well as their analytical value to making sense of what and how people do (interact) online. A case study is used to provide baseline data for framing the notion of digital remains or traces of virtual settlements, the form they take in today's social web and the means through which they are revealed and made sense of using social visualization techniques. It turns out that virtual excavations organized around cultural artifacts of practice can provide valuable insight, not only into structural properties of 'social' technologies and the way in which they are appropriated, but also dynamic aspects of the enacted cyber-structures resulting from recurrent co-engagement and online collaboration.